Diary of a wimpy kid : dog days - Kinney, Jeff (New York : Abrams, 2009)
In the latest diary of a middle-schooler Greg Heffley, he records his attempts to spend his summer vacation sensibly indoors playing video games and watching television, despite his mother's other ideas.
Keywords: Summer -- Fiction; Diaries -- Fiction